Volume 1: Aircraft Engine; Marine; Turbomachinery; Microturbines and Small Turbomachinery 1993
DOI: 10.1115/93-gt-139
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study of the Time-Dependent Pressure Response of a Shock Wave Oscillating in a Nozzle

Abstract: Investigations of flutter in transonic turbine cascades have shown that the movement of unsteady normal shocks has an important effect on the excitation of blades. In order to predict this phenomenon correctly, detailed studies concerning the response of unsteady blade pressures versus different parameters of an oscillating shock wave should be performed, if possible isolated from other flow effects in cascades. In the present investigation the correlation between an oscillating normal shock wave and the respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Some experimental and numerical studies have been carried out using a variablegeometry second throat to investigate the effects of downstream periodic pressure perturbations on shocks (see for example Sajben & Kroutil 1981;Ott, Bolcs & Fransson 1995;Handa, Masuda & Matsuo 2003;Bur et al 2006). All have reported that the amplitude of shock oscillation decreases with increasing perturbation frequency, although the reasons for this are not discussed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Some experimental and numerical studies have been carried out using a variablegeometry second throat to investigate the effects of downstream periodic pressure perturbations on shocks (see for example Sajben & Kroutil 1981;Ott, Bolcs & Fransson 1995;Handa, Masuda & Matsuo 2003;Bur et al 2006). All have reported that the amplitude of shock oscillation decreases with increasing perturbation frequency, although the reasons for this are not discussed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…For this configuration, the shock-wave position and the post-shock pressure-recovery cannot be predicted by 2-D computations [82][83][84]. Indeed, because of the relatively small width of the nozzle and the rather thick sidewall boundary-layers, only 3-D viscous computations can correctly predict this flow, where the shock-wave position is dominated by the corner-flow/shock-wave Table III in Chassaing et al [72]).…”
Section: Configuration Studiedmentioning
confidence: 84%
“…The time-linearized time-harmonic method is evaluated through comparison with measurements [81,82] and with previous time-nonlinear computations [72,83] in a 3-D nozzle experimentally and computationally investigated by Ott et al [82] (Figure 1). The facility, with a width of 40 mm, was equipped with nozzle liners giving a converging-diverging section.…”
Section: Configuration Studiedmentioning
confidence: 99%
See 2 more Smart Citations